2011
DOI: 10.5334/jbr-btr.525
|View full text |Cite
|
Sign up to set email alerts
|

Arrested pneumatization of the skull base

Abstract: Background:A 24-year-old woman was referred to a neurologist by her general practitioner, because of complaints of headaches and photophobia with intermittent nausea and vomiting for several years. Physical, neurological and laboratory investigations were unremarkable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…3,6 De Jong et al reported in a case presentation that for several years their patient suffered headache, photophobia, intermittent nausea, and vomiting, but no characteristic feature was identified from physical, neurologic, and laboratory findings. 5 In our cases also, arrested pneumatization was incidentally identified at diag-nostic imaging examination for various disease entities. While one case was being examined for reasons of left sixth nerve paralysis and headache, lesion identification on the sphenoid bone led to contrast-enhanced MR assessment but no enhancement was identified.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…3,6 De Jong et al reported in a case presentation that for several years their patient suffered headache, photophobia, intermittent nausea, and vomiting, but no characteristic feature was identified from physical, neurologic, and laboratory findings. 5 In our cases also, arrested pneumatization was incidentally identified at diag-nostic imaging examination for various disease entities. While one case was being examined for reasons of left sixth nerve paralysis and headache, lesion identification on the sphenoid bone led to contrast-enhanced MR assessment but no enhancement was identified.…”
Section: Discussionsupporting
confidence: 53%
“…It generally manifests itself in the basisphenoid bone and pterygoid process region, 3,4 with the petrous temporal apex and clivus also being reported areas. 5,6 In fact, accessory pneumatization areas such as the occipital and frontal bones, as well as the maxillary bone, have also been defined. 3,4 However, in the ethmoid bone, arrested pneumatization has not been defined, likely due to its aeration mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case highlights how this entity can easily be mistaken for more sinister skull base lesions. Although it is noted that other cases have been identified during the assessment of patients with headache, 3 given the anecdotal nature of the case, it is hard to know the relevance of the resolution of the patient's headache after surgery. In the case of refractory headache and APSB, endoscopic surgery to open the cavity may be a consideration.…”
Section: Figurementioning
confidence: 99%
“…Subsequent discussion with other subspecialists highlighted the poor recognition of this phenomenon. While there are publications on this phenomenon elsewhere in the scientific literature, [1][2][3] there is a paucity in the otolaryngology and general surgical literature. 4 Recognition of variant anatomy by surgeons is crucial in order to avoid unnecessary investigations and interventions.…”
mentioning
confidence: 99%